Legal Inconsistencies in the Criminalization of Fraud: Toward a Harmonized International Criminal Framework - Iqbal, Mochamad; Maryano, Maryano; Darodjat, Tubagus Achmad (Journal Evidence Of Law, 2025)
Fundamental differences in the definitions, criminalization, and enforcement procedures of transnational fraud have created significant obstacles to international criminal law cooperation. This study aims to identify legal inconsistencies in twelve jurisdictions and to formulate a normative harmonization framework applicable to the handling of transnational fraud. Through a comparative legal approach and doctrinal analysis, the study finds that regulatory fragmentation not only weakens the effectiveness of law enforcement but also hinders the restoration of victims’ rights and the application of substantive justice principles. This study proposes an integrated framework encompassing universal definitions, minimum procedural standards, and victim-centered cooperation mechanisms. These findings are expected to serve as a conceptual foundation for developing more inclusive and responsive international legal instruments to address the challenges of transnational fraud.